Dualité sémantique des expressions figées et mécanismes de décodage du sens idiomatique - Sułkowska, Monika (Neophilologica, 2019)
The paper focuses on the double nature of phraseological relations in terms of their semantics and the mechanisms and theoretical frameworks that concern the reception of idiomatic meanings. The author presents the concept of the double meaning of phraseological structures and selected questions related to the description of semantics within phraseology. The latter part of the paper is devoted to various models of reception and understanding of idiomatic meanings.